The alchemy of facilitation revealed through individual stories and collective narrative. Issue 1 (2nd January 2017) - McCormack, Coralie; Gilchrist, John; Hancock, Eleanor; Islam, Jesmin; Kennelly, Robert; Northcote, Maria; Thomson, Kate
Abstract: Facilitation is a key 'ingredient' in the success and sustainability of communities of practice. Yet, little attention has been given to in situ experiences of facilitators of these communities. This paper takes up the challenge to explore these experiences using reflective stories written by seven TATAL (Talking about Teaching and Learning) facilitators (the authors) from different disciplines in five different Australian universities. The authors' collaborative analysis of their experiences suggests reframing the role of facilitator to include the role of alchemist, a promoter of transformation. This reframing has the potential to change the way higher education community of practice facilitators think about and enact their role. The story-based reflective process used in this self-study could also be used by facilitators to investigate their own practice, as a component of facilitator education programmes or by academics and researchers in other contexts who seek a participatory, collaborative approach to evaluate their practice.